A phase 2 study of lenvatinib in patients with RET fusion-positive lung adenocarcinoma. (December 2019) - Hida, Toyoaki; Velcheti, Vamsidhar; Reckamp, Karen L.; Nokihara, Hiroshi; Sachdev, Pallavi; Kubota, Tomoki; Nakada, Takuya; Dutcus, Corina E.; Ren, Min; Tamura, Tomohide
Highlights: Lenvatinib had antitumor activity in RET fusion-positive lung adenocarcinoma. The safety profile in this study was similar to prior reports with lenvatinib. The observed median progression-free survival of 7.3 months appears promising. Abstract: Objectives: Despite improved outcomes associated with immunotherapies for non-small cell lung cancer (NSCLC), many patients do not respond to treatment. Therefore, there is still an unmet need for molecularly targeted therapies in this patient population. Fusions of the RET oncogene have been identified as driver alterations in patients with NSCLC. Lenvatinib is a multityrosine kinase inhibitor of vascular endothelial growth factor receptors 1–3, fibroblast growth factor receptors 1–4, RET, and other targets. This study evaluated the safety and efficacy of lenvatinib in patients with RET fusion-positive lung adenocarcinoma. Materials and methods: In this phase 2, multicenter, open-label study (NCT01877083), patients with RET -positive lung adenocarcinoma received oral lenvatinib 24 mg/day. The primary end point was objective response rate (ORR) by investigator review per Response Evaluation Criteria In Solid Tumors v1.1 criteria. The secondary end points included safety and tolerability, progression-free survival (PFS), and overall survival (OS). Results: Of 536 patients who screened for study inclusion and exclusion, 25 patients with RET translocations ( KIF5B-RET [n = 13] and CCDC6-RET [n = 12]) were identified and received lenvatinib. The overall ORR was 16% (95% CI: 4.5%–36.1%). At data cutoff (February 3, 2016), the median PFS was 7.3 months (95% CI: 3.6–10.2) and the median OS was not reached. Duration of response was not estimable at the time of data cutoff. All patients experienced a treatment-emergent adverse event (TEAE); 23 (92%) patients experienced a TEAE of ≥ grade 3, and 6 (24%) patients discontinued lenvatinib due to a TEAE. The most common TEAEs were hypertension (68%), nausea (60%), decreased appetite (52%), diarrhea (52%), and proteinuria (48%). Conclusions: Lenvatinib demonstrated activity in patients with RET fusion-positive lung adenocarcinomas; although the response rate was relatively low, the median PFS supports the activity of lenvatinib in these patients.